Role of Metronidazole after Appendicectomy in Simple Cases of Acute Appendicitis - M. Umair Samee, Muhammad Afzal, Aurangzeb Khan, Khalid Abaidullah, Hafiz Muhammad Abdullah, Ejaz Iqbal, Fahad Ahmed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Simple cases of acute appendicitis are usually dealt with appendicectomy and post-operative antibiotics. Causative organisms include both aerobes as well as anaerobes. The antibiotic spectrum to cover aerobes varies from hospital to hospital but the drug Metronidazole is used to cover anaerobes which is fairly common Aim: To determine the role of metronidazole after appendicectomy in simple cases of acute appendicitis Study design: Randomized, controlled, multicenter trial. Place and duration of study: Department of Surgery, Central Park Teaching Hospital Lahore, Noor Hospital, Kot Radha Kishan and Bilquees Hospital, Kasur from 1st January 2020 to 31st December 2021 Methodology: One hundred and thirty patients were included in the study divided into 2 groups (65 in each group). Inclusion criteria included all patients of simple acute appendicitis from age 13 to 70 years. Exclusion criteria were patients with complications of acute appendicitis. Patients receiving Metronidazole were allocated group A, while those not receiving this drug were allocated group B. Open appendicectomy was done in all cases. Variables of interest were post-operative wound infection, hospital stay and nausea/vomiting. Results: Mean age of patients of group A was 29.39±16.32 years while mean age of patients in group B was 34.18±18.05 years. 44.6% patients of group A were male and 55.4% were females. On the other hand 50.8% patients of group B were male and 49.2% were females. In group A, 6 patients got wound infection (9.2%) while 59 patients had uneventful recovery (90.8%). In group B, 4 patients got wound infection making it 6.2% while rest of the 61 patients had uneventful recovery (93.8%). The difference between the 2 groups was not statistically significant (p-value 0.11). Mean hospital stay in group A patients was 2.28±0.89 days while in group B it was 2.12±0.73 days. Conclusion: Metronidazole is an effective drug against anaerobes but in simple cases of non-perforated appendicitis this drug does not decreases the wound infection rate after appendicectomy. Keywords: Metronidazole, Appendicitis, Appendicectomy